From the bench of molecular understanding to the bedside of optimal therapy for BCR::ABL1 and ABL-class acute lymphoblastic leukemia in children and adolescents - Sarah K. Tasian; Judith M. Boer; Monique L. den Boer (EJC Paediatric Oncology, 2025)
This review aims to discuss similarities and dissimilarities between BCR::ABL1-rearranged (Philadelphia chromosome-positive [Ph+]) and ABL-class fusion-driven BCR::ABL1-like (Ph-like) acute lymphoblastic leukemia (ALL) in children and adolescents. Recent insights into the biology of these historically high-risk leukemias, modern laboratory diagnostics, current treatment approaches, potential causes of treatment failure, emerging new targeted therapies and immunotherapeutic approaches for patients will be discussed. While the primary focus of this review is upon children and adolescents with BCR::ABL1-positive and ABL-class ALL, extended knowledge from recent adult clinical trials will also be addressed.